Development of new preclinical models to advance adrenocortical carcinoma research. Issue 4 (April 2018) - Kiseljak-Vassiliades, Katja; Zhang, Yu; Bagby, Stacey M; Kar, Adwitiya; Pozdeyev, Nikita; Xu, Mei; Gowan, Katherine; Sharma, Vibha; Raeburn, Christopher D; Albuja-Cruz, Maria; Jones, Kenneth L; Fishbein, Lauren; et al.
Abstract : Adrenocortical cancer (ACC) is an orphan malignancy that results in heterogeneous clinical phenotypes and molecular genotypes. There are no curative treatments for this deadly cancer with 35% survival at five years. Our understanding of the underlying pathobiology and our ability to test novel therapeutic targets has been limited due to the lack of preclinical models. Here, we report the establishment of two new ACC cell lines and corresponding patient-derived xenograft (PDX) models. CU-ACC1 cell line and PDX were derived from a perinephric metastasis in a patient whose primary tumor secreted aldosterone. CU-ACC2 cell line and PDX were derived from a liver metastasis in a patient with Lynch syndrome. Short tandem repeat profiling confirmed consistent matches between human samples and models. Both exomic and RNA sequencing profiling were performed on the patient samples and the models, and hormonal secretion was evaluated in the new cell lines. RNA sequencing and immunohistochemistry confirmed the expression of adrenal cortex markers in the PDXs and human tumors. The new cell lines replicate two of the known genetic models of ACC. CU-ACC1 cells had a mutation in CTNNB1 and secreted cortisol but not aldosterone. CU-ACC2 cells had a TP53 mutation and loss of MSH2 consistent with the patient's known germline mutation causing Lynch syndrome. Both cell lines can be transfected and transduced with similar growth rates. These new preclinical models of ACC significantly advance the field by allowing investigation of underlying molecular mechanisms of ACC and the ability to test patient-specific therapeutic targets.